2004
DOI: 10.1021/es0342704
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Diffusion Coefficient of Chromium in Colloidal Silica Using Digital Photography

Abstract: In order to study the effectiveness of using colloidal silica, NYACOL DP5110, to stabilize chromium-contaminated soil, the diffusion of chromium in colloidal silica gel was estimated from laboratory experiments. To measure diffusion coefficients of chromium in the colloidal silica gel, a new measurement method based on digital photography was introduced. A series of experiments were designed and conducted to validate this new method and to estimate the diffusion coefficients of chromium in the colloidal silica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 16 publications
(25 reference statements)
0
16
0
Order By: Relevance
“…24,39,41 The porewater in gelled colloidal silica also has an elevated pH, potentially enhancing retention of Sr and Cs through increasing surface complexation to (clay) minerals and the silica nanoparticles (20,21,(36)(37)(38). 24,25,38,39,41 However, a high ionic strength due to a saline accelerant used to induce gelling 5,42 could cause (increased) competition between cations in the accelerant with contaminants for surface complexation processes 41 inducing the release of Sr and Cs from mineral components into the colloidal silica porewater. This could lead to diffusion of contaminants through the gelled materials 42 and subsequent release of radionuclides into the groundwater.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,39,41 The porewater in gelled colloidal silica also has an elevated pH, potentially enhancing retention of Sr and Cs through increasing surface complexation to (clay) minerals and the silica nanoparticles (20,21,(36)(37)(38). 24,25,38,39,41 However, a high ionic strength due to a saline accelerant used to induce gelling 5,42 could cause (increased) competition between cations in the accelerant with contaminants for surface complexation processes 41 inducing the release of Sr and Cs from mineral components into the colloidal silica porewater. This could lead to diffusion of contaminants through the gelled materials 42 and subsequent release of radionuclides into the groundwater.…”
Section: Introductionmentioning
confidence: 99%
“…24,25,38,39,41 However, a high ionic strength due to a saline accelerant used to induce gelling 5,42 could cause (increased) competition between cations in the accelerant with contaminants for surface complexation processes 41 inducing the release of Sr and Cs from mineral components into the colloidal silica porewater. This could lead to diffusion of contaminants through the gelled materials 42 and subsequent release of radionuclides into the groundwater. Thus, a comprehensive understanding of these competing impacts on the geochemistry, fate, mobility and speciation of contaminants, such as Sr and Cs, is required to underpin the use of nanoparticulate colloidal silica materials for contaminant control.…”
Section: Introductionmentioning
confidence: 99%
“…, SG has 100% removal efficacy for removal of Cr(VI) present in water at pH 5.0. Tantemsapya and Meegoda conducted studies using colloidal silica to treat chromium contaminated soil and reported that chromium adsorbed to colloidal silica gel and diffusion coefficient of colloidal silica gel ranges from 1.76 to 8.48 x 10 −10 m 2 /s and is dependent on pH and silica concentration. However, in the present study, the reduction experiments were carried out with native COPR sample without altering the pH since it was not a feasible option, considering the quantum of COPR present in the selected site.…”
Section: Resultsmentioning
confidence: 99%
“…const.mol Ion diffusion coefficient1.32 Pan et al. (2002) and Tantemsapya and Meegoda (2004)Assumed the values for dead and live cells are the same…”
Section: Model Descriptionmentioning
confidence: 99%